Comparison of Storability and Sensory Assessment of Wet Noodles with the Addition of Melinjo Leaf Extract (Gnetum gnemon L) as a Natural Preservative - Lestari, Ayu Wiji; Akhmad Mutohhar,; Akhmad Faried Yusuf ,; Iffah Muflihati,; Sari Suhendriani, (Jurnal Sains Boga, 2024)
Wet noodles are raw noodles that require cooking by boiling in boiling water before consumption. The water content in wet noodles ranges from 52-60%. High water content causes wet noodles cannot be stored for a long time. One of the natural ingredients that can be used as a preservative is melinjo leaves. The purpose of this study was to determine the effect of natural preservatives from melinjo leaf extract on the shelf life of wet noodles. Using a one-factor completely randomized design (CRD) with different ages of melinjo leaves, namely young leaves, old leaves, dry leaves, and also a mixture of the three. The extraction process is carried out through the maceration method. The solvent used in this extraction is distilled water. From the results of the research on the shelf life of wet noodles, the best shelf life analysis was found in the treatment of young leaves, namely 24 hours, testing the water content with the results for each treatment of young leaves 54.7%, old leaves 49.07%, dry leaves 48, 8% , mix 53.8%. The color test on the brightness parameter (L) was the highest on old leaves 69.42, the redness level parameter (a) was the highest on the control 4.17 , the redness level parameter (b) was the highest on the mixture 17.28. The organoleptic test showed that the wet noodles with each treatment with the addition of melinjo leaf extract were not significantly different. The hedonic test of wet noodles was acceptable to the panelists with an average value of color 4.00, aroma 3.50, taste 3.84, texture 4.00, appearance 3.98.